2011
DOI: 10.1007/978-1-4614-0216-9_36
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Modeling of Ballistic Impact on Kevlar 49 Fabrics

Abstract: This paper presents an improved material model suitable for Kevlar 49 fabric which was implemented into the commercial explicit Finite Element (FE) software LS-DYNA through a user defined material subroutine (UMAT). The fabric constitutive behavior in the current material model was obtained from new experimental data in the principal material directions (warp and fill) under static loading. Two different modeling configurations, i.e. single FE layer and multiple FE layers were used to simulate the ballistic te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…[7] have achieved experimental testing and theoretical modeling regarding the tensile behavior of the 3D angle-interlock woven (3D-A) fabric under high strain rates. Before this study, high-strain rate tensile tests about woven fabrics only confined to 2D woven fabric structures, especially on plain woven fabric, have been reported in several literature [7678]. From Figure 4, it could be found that the tensile fracture mechanism of the 3D-A fabric under quasi-static loading was different from that under high-speed condition.…”
Section: Mechanical Characterizations Of 3diwfsmentioning
confidence: 91%
“…[7] have achieved experimental testing and theoretical modeling regarding the tensile behavior of the 3D angle-interlock woven (3D-A) fabric under high strain rates. Before this study, high-strain rate tensile tests about woven fabrics only confined to 2D woven fabric structures, especially on plain woven fabric, have been reported in several literature [7678]. From Figure 4, it could be found that the tensile fracture mechanism of the 3D-A fabric under quasi-static loading was different from that under high-speed condition.…”
Section: Mechanical Characterizations Of 3diwfsmentioning
confidence: 91%